The Role of Folk Motifs and National Patterns in Developing Students’ Creativity in Visual Arts Education - Raxmonova Mahliyo Zoir qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article discusses the significance of integrating folk motifs and national patterns into visual arts education. It examines how using traditional designs enhances students’ creative thinking, aesthetic skills, and cultural understanding. The paper also explores pedagogical strategies for effectively incorporating folk art elements into contemporary classroom practices.